Plaque Assay for Measuring Serum Bactericidal Activity Against Gonococci - Corbeil, Lynete B. (1978)
A new semiquantitative plaque assay was developed to measure killing of gonococci by serum. Results compare well with an established quantitative method, but the plaque assay is faster, simpler, and less expensive.